Digital twins in personalized medicine: Insights from a systematic review - Uğraş, Ebru (The European Research Journal, 2025)
Objectives: Digital twins (DTs) are increasingly recognized as valuable tools in the advancement of personalized medicine (PM). Methods: This systematic review explores the current landscape of DT applications across medical domains, focusing on their feasibility, benefits, challenges, and potential future roles. Following PRISMA guidelines, literature was sourced from PubMed and Scopus using clearly defined inclusion and exclusion criteria, resulting in 14 studies eligible for full-text review. Results: Findings show that DTs are being utilized in various specialties such as cardiology, geriatrics, radiology, and oncology, offering advantages in cost reduction, treatment precision, and patient outcomes. However, key challenges remain, including data privacy, technical integration, ethical considerations, and the need for interdisciplinary collaboration. Conclusions: This systematic review offers a comprehensive synthesis of how DTs are being integrated into PM and highlights areas requiring further empirical research to support wider implementation.